Digital Advertisement: A BLE Beacon Based Application - K.P. Swain, Soumya Ranjan Samal, IS Amiri, M.N. Mohanty, G. Palai (International Journal of Advanced Science and Technology, 2020)
Advertisement is a crucial part of daily life for both businesses and general public. It creates awareness about a product or provides information to consumers. There are various forms of advertisement such as paper and pamphlets, digital advertisement through social media such as facebook, twitter, instagram, Whatsapp etc. One form of digital advertisement is through BLE beacon. BLE or Bluetooth Low Energy is a technology which advertises its programmed data or information when powered on. Harnessing this capability, beacons can be used to target customers directly using their smart phone. As the advertising medium need not required to buy a rented advertisement space, it is mostly used in digital marketing. BLE is also widely implemented in IoT for exchanging information in short distances. In this work, BLE beacon is implemented in a college premises for making advertisement about its different important department or laboratory. A mobile app is developed which interacts with mobile devices with a particular ID and after authentication, the advertising information is pushed into the various smartphones present nearby.